SALES PROMOTION TECHNIQUE IN SALES AND MARKETING DEPARTMENT HOTEL NOVOTEL PEKANBARU - Anshori, M Faisal; ", Musadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine Sales Promotion Techniques on sales volume and guest responses to products promoted by sales. This research was conducted at a four-star hotel (****), namely the Novotel Hotel Pekanbaru, Riau Province. The research method used in this research is quantitative descriptive method. To find out the responses of respondents with interview data collection techniques, questionnaires, observation and documentation. The results of this study, concluded that sales promotion techniques in the sales and marketing department of Novotel Pekanbaru Hotel is Good.Â Keywords: Promotion techniques, Guest Response, Sales and Marketing Â